1983
DOI: 10.3171/jns.1983.59.4.0627
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular morphine for control of pain in terminal cancer patients

Abstract: Satisfactory control of intractable pain has been achieved in 17 terminal cancer patients by injecting small doses of morphine into the lateral cerebral ventricle via an Ommaya reservoir. Pain relief together with a favorable behavioral response was obtained without interference with other sensory modalities, noticeable physical changes, or side effects annoying or severe enough for the patient to discontinue therapy. Eleven patients developed tolerance, but this phenomenon does not require withdrawal of treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Morphine has been used widely to relieve patients of intractable pain during the terminal phase of cancer [25]. From our experience, we confirm that morphine may also be helpful against respiratory distress following WD.…”
Section: Discussionsupporting
confidence: 69%
“…Morphine has been used widely to relieve patients of intractable pain during the terminal phase of cancer [25]. From our experience, we confirm that morphine may also be helpful against respiratory distress following WD.…”
Section: Discussionsupporting
confidence: 69%
“…In addition, this type of experimental model is in agreement with the requirement of the Ethical Commission for the Study of Pain in Animals [17,18]. Group 4 rats re ceived morphine chloride (Navarro SA®; 30 pg/kg, the average dose used in humans [19,20] through an ICV cannula), since it has been reported that ICV administration of morphine induces a more intense and longer analgesia than others routes [19,20], Group 5 consisted of rats receiving naloxone (Abello SA®) by intramuscular injection (l ug/kg), the specific dose used in humans [21], Group 6 consisted of rats submitted to a painful stimulus and receiving morphine chloride through an ICV cannula. Group 7 were rats submitted to a painful stimulus and receiving naloxone.…”
Section: Methodsmentioning
confidence: 81%
“…Mi nor and transient side effects, like nausea, vomiting, skin reactions and itching, occurred with the same rate in both [6,8]. Transient urinary re tention is more specific for spinal administration [2,6,10], whereas reversion behavior disorders or dysphoria were significantly reported after intraventricular infusion [7,14].…”
Section: Discussionmentioning
confidence: 99%
“…Paradoxically, the risks of central respiratory depression are rela tively high after intraventricular administration of low doses of mor phine [6,7,12,14] and can be immediately reversed by naloxone. But all these patients have already received morphine systematically and as a result must have reduced sensitivity of opiate receptors [5,6,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation